The Oral mucormycosis in post-COVID-19 patients: A case series - Dr. Shamli Sadawarte, Dr. Shamli Sadawarte; Kharwade, Dr. Neha N. Kharwade; Bangar., Dr. Sayojyata S. Bangar.; Dr. Mangala R., Dr. Mangala R.; Paraye., Dr. Swati Paraye.; avidson., Dr. S. Sam Pororaj Davidson. (Indian Journal of Case Reports, 2022)
The rise of mucormycosis in COVID-19 patients is predisposed by indiscriminate intake of corticosteroids, poorly controlled diabetes, injury, the prolonged neutropenia, organ transplant, hemopoietic malignancies, prolonged stays in the intensive care unit and due to nosocomial infection (Raut &Huy, 2021).Oral lesions seen in COVID-19 patients are more probably caused by co-infections, adverse reactions, immunocompromised conditions instead of direct COVID-19 infection. Not every mucormycosis that occurs in the pandemic times is due to COVID-19.We would like to report 4 post-COVID-19 patients who had oral mucormycosis after covid recovery period.